Is the AJCC TNM staging system still appropriate for gastric cancer patients survival after 5 years?. Issue 6 (June 2019) - Lin, Jian-Xian; Lin, Jun-Peng; Xie, Jian-Wei; Wang, Jia-Bin; Lu, Jun; Chen, Qi-Yue; Cao, Long-Long; Lin, Mi; Tu, Ru-Hong; Zheng, Chao-Hui; Huang, Chang-Ming; Li, Ping
Abstract: Purpose: The aim of this study was to evaluate the prognostic value of the eighth AJCC TNM staging classification for patients with gastric cancer who had already survived for 5 years. Patients and methods: Patients who underwent radical gastrectomy at a large eastern center were considered. The prognostic value of staging systems were assessed and compared. Additional external validation was performed using a dataset from the Surveillance, Epidemiology, and End Result (SEER) database. Results: The 5-year overall survival (OS) rate for patients in the training set was 59.4%. With the prolongation of the survival time after surgery, the 5-year OS improved significantly (P < 0.05). However, there were no significant differences in survival curves among patients who have survived 5 years after surgery. The AUC and χ2 of the eighth AJCC classification for predicting of 5-year OS decreased gradually after surgery and appeared stable after 5 years. For patients who survived 5 years after surgery, we constructed a new TNM staging system (nTNM) according to the survival curves of T stage and N stage. A 2-step multivariate analysis showed that nTNM, age and sex were independent prognostic factors. The nTNM demonstrated superior prognostic stratification, with higher c-statistic and likelihood ratio chi-square scores and lower AIC values than those of the AJCC classification. Similar results were observed in the external validation set. Conclusion: The nTNM predicted an additional survival more accurately than did the AJCC classification for patients who have survived 5 years after surgery; this may guide decisions regarding surveillance.